2008
DOI: 10.1063/1.2987420
|View full text |Cite
|
Sign up to set email alerts
|

ZnO based oxide system with continuous bandgap modulation from 3.7 to 4.9 eV

Abstract: ZnO based oxide system Zn1−x−yBexMgyO has been prepared by pulsed laser deposition. By incorporating different amounts of beryllium and magnesium into ZnO, the bandgap of ZnBeMgO has been modulated from 3.7 to 4.9 eV continuously. The crystal quality of ZnBeMgO film has been improved significantly comparing with that of either ZnMgO or BeZnO. These ZnBeMgO films are promising for fabricating high-efficiency optoelectronic devices such as solar-blind UV detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…In order to realize such optoelectronic devices with high efficiency, a crucial step is the realization of band gap engineering by alloying to create barrier layers and quantum wells (QWs) in device heterostructures [3]. Many works have been reported on ZnMgO [4], ZnCaO [5,6], and ZnBeO [7,8], which are wide band gap semiconductors, for application in quantum well-related devices and other fields from the viewpoint of band gap engineering as well as p-n junctions [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize such optoelectronic devices with high efficiency, a crucial step is the realization of band gap engineering by alloying to create barrier layers and quantum wells (QWs) in device heterostructures [3]. Many works have been reported on ZnMgO [4], ZnCaO [5,6], and ZnBeO [7,8], which are wide band gap semiconductors, for application in quantum well-related devices and other fields from the viewpoint of band gap engineering as well as p-n junctions [9].…”
Section: Introductionmentioning
confidence: 99%
“…7,[10][11][12][13] The advantage of this quaternary system is that Mg has a much larger covalent radius (1.41 Å ) 6 than Be and can compensate for the large lattice mismatch between ZnO and BeO. Therefore, it is expected that by tuning the compositions of both BeO and MgO in ZnO (i.e., Be/Mg ratio), one can achieve lattice matching to ZnO, prevent phase separation, and achieve wider bandgaps.…”
Section: Introductionmentioning
confidence: 99%
“…void of phase separation, as compared to ternary MgZnO or BeZnO alloys. For certain growth conditions quaternary layers with sufficiently large bandgaps up to 4.9 eV [8] have been achieved. Theoretical studies of bandgap variation and equilibrium lattice parameters for the quaternary BeMgZnO system have been performed mainly using density functional theory (DFT), known to significantly underestimate the bandgap [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, use of nominal high temperatures for attaining quality material, the bandgap tuning is limited because of phase segregation for Mg contents above 33% induced by structural mismatch between the wurtzite ZnO and rock salt MgO [7]. To overcome this limitation, quaternary BeMgZnO has been proposed [1,8,9]. As initial experiments and theoretical studies revealed, co-alloying of ZnO together with BeO and MgO results in more stable wurtzite structure, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation